Kajian Tarif Angkutan Umum Bus Damri Rute BIL – Kota Matram Berdasarkan Biaya Operasional Kendaraan - Titik Wahyuningsih (Jurnal Planoearth, 2020)
The increasing amount of people traveling in the city of Mataram causes the demand for satisfactory public transportation both in terms of quantity and quality. Damri Bus is one of the transportation that provides passenger public transportation services with one of the routes, specifically Lombok International Airport (LIA) - Mataram. The purpose of this research is to find out how much the Damri Bus passenger transportation rates are based on vehicle operating costs (VOC) route BIL - Mataram. The method used to analyze passenger transportation rates based on VOC is using the PCI (Pacific International Consultant) method. Based on the results of the analysis, it is known that the Damri Bus VOC is Rp 2,788,439, while the results of the data analysis based on the VOC obtained average rates in the Morning is Rp15,015, in the Noon is Rp 13,223 and in the Afternoon is Rp 42,262, with an average tariff is Rp 23,499 , 89. The actual tariff of Damri Bus routes BIL - Mataram is Rp. 30,000, the results show that the results of the tariff analysis with the actual tariff are still appropriate.